The Quality of Life of Young Children and Infants with Chronic Medical Problems: Review of the Literature - Payot, Antoine; Barrington, Keith J. (Current problems in pediatric and adolescent health care, 2011)
The question “what makes a good quality of life?” is a philosophical one which could be thought immune to scientific investigations. However, over the last few decades there has been great progress in developing tools to quantify quality of life (QoL) to make comparisons between different health states, evaluate the effectiveness of medical interventions, and describe the life trajectories of individuals or groups. Using a series of vignettes, we explore and review the biomedical literature to demonstrate how QoL is affected by chronic health conditions in childhood, and how it evolves as individuals pass into adulthood. Individuals experiencing serious chronic illnesses generally have reduced health-related QoL: their health status has significant repercussions of their everyday life, but scores are usually much better than healthy individuals expect, and better than physicians predict. Global QoL is more than a health status concept. QoL is a complex relationship between objectivity and subjectivity; it requires substantial and valid facts, and it defines itself by an interpretation of health within different schemes of values: societal, medical, and those of the subject themselves. QoL is dynamic; purely physical influences diminish as individuals age, and psychosocial factors become much more important. Resilience frequently allows adaptation to adverse health states, leading to acceptable QoL for most children with disabilities.